2018
DOI: 10.5267/j.ijiec.2017.7.001
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous improvement of surface quality and productivity using grey relational analysis based Taguchi design for turning couple (AISI D3 steel/ mixed ceramic tool (Al2O3 + TiC))

Abstract: Current optimization strategies are based on the increase the productivity and the quality with lower cost in short time. Grey relational analysis "GRA" based on Taguchi design was proposed in this paper for simultaneous improvement of surface quality and productivity. The turning trials based on mixed Taguchi L18 factorial plan were conducted under dry cutting conditions for the machining couple: AISI D3 steel/mixed ceramic inserts (CC650). The machining parameters taken into account during this study are as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Zerti et al. 21 applied an efficient multiobjective optimization technique named as gray relational analysis (GRA) based on a Taguchi design in order to optimize simultaneously two important factors (surface quality and productivity) that represent an index of manufacturer's qualification. The tool-material pair used in this study is AISI D3 steel/mixed ceramic tool.…”
Section: Introductionmentioning
confidence: 99%
“…Zerti et al. 21 applied an efficient multiobjective optimization technique named as gray relational analysis (GRA) based on a Taguchi design in order to optimize simultaneously two important factors (surface quality and productivity) that represent an index of manufacturer's qualification. The tool-material pair used in this study is AISI D3 steel/mixed ceramic tool.…”
Section: Introductionmentioning
confidence: 99%
“…An ANN is a data processing and modeling technique works similarly to the human brain, ANNs are very efficient on adaptation and learning and capable to model the highly nonlinear processes. for this reason, they are used as modeling tools in a number of applications [15,16,20,22] .…”
Section: Ann Modelingmentioning
confidence: 99%
“…Nouioua et al [20] , Kilickap et al [21] , Zerti et al [22] developed ANN and RSM models to predict outputs parameters, the authors found that artificial neural network models show better accuracy than response surface methodology with low error, which justifies the conclusion that concerns the high precision of the ANN compared to the RSM.…”
Section: Introductionmentioning
confidence: 97%
“…It can be used for optimizing material removal rate, electrode wear and surface roughness responses in PMEDM (Tripathy & Tripathy, 2017). Material removal rate (MRR), surface roughness and fractal dimension are also responses to optimize when machining AISI D2 tool steel (Prabhu & Vinayagam, 2016;Zerti et al, 2018). The results showed that voltage has the strongest effect (42.42 %) and pulse on time has the smallest effect (11.13%).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, many other methods have also been used as Artificial neural network, Response surface methodology, and Taguchi's combination with other methods (GRA, MOORA-PCA, VIKOR, multiple response signal-to-noise, weighted signal-to-noise,...) for multi-target optimization in EDM (Tirumala et al, 2018;Munmun & Kalipad, 2017;Bhaumik & Maity, 2017;Nayaka et al, 2017;Munmun & Kalipada, 2017;Dey & Chakraborty, 2015). However, Taguchi-TOPSIS and Taguchi-GRA are the most commonly used (Kumar et al, 2018;Zerti et al, 2018;Mohapatraa et al, 2017). Dastagiri et al (2016) have shown that TOPSIS-Taguchi is more effective than Taguchi-GRA in multi-response optimization of PMEDM.…”
Section: Introductionmentioning
confidence: 99%